Ivabradine rescues vascular abnormalities in a mouse model of duchenne muscular dystrophy. (10th June 2022) - Acar, E; Kuruppu Appuhamilage, M; Szabo, PL; Trojanek, S; Abraham, D; Hilber, K; Podesser, BK; Kiss, A
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Fonds zur Förderung der wissenschaftlichen Forschung Ivabradine rescues vascular abnormalities in a mouse model of muscular dystrophy Background: Duchenne muscular dystrophy (DMD) is a rare genetic disorder that primarily affects boys, initiated by the absence of dystrophin and is mainly differentiated by skeletal muscle degeneration and cardiac dysfunction. However, recent studies have underlined the importance of vascular abnormalities such as augmented arterial stiffness and endothelial dysfunction in the progression of cardiac complications in DMD. Several pleiotropic effects of ivabradine have been identified, including the reduction of vascular complications in coronary artery and ischemic heart disease patients. Nevertheless, whether chronic ivabradine treatment could improve the vascular complications in DMD is largely unknown. Methods: In this study, vascular abnormalities in both dystrophin and utrophin deficient (mdx-utr KO) mice were examined, a severe and progressive animal model of DMD. Mice (4-6 weeks old) were subjected to ivabradine (10 mg/kg/day in drinking water) or vehicle treatments for 3 to 4 weeks. At the end of the treatment, aorta and lung tissue were collected to assess the vascular reactivity by wire myograph and the activity of angiotensin-converting enzyme (ACE) activity was measured in lung tissue respectively. Results: Comparable with DMD patients, mdx-utr KO mice also exhibit vascular abnormalities and cardiac fibrosis. Ivabradine-treated mice showed a significantly improved endothelium-dependent vasodilation (p<0.05) and decreased vascular stiffness compared to vehicle-treated animals (p<0.01). In addition, lung ACE activity was significantly reduced in the treated mice in comparison to the control group (p<0.01) indicating less activation in the renin-angiotensin-aldosterone system, which causative plays role in the progression of vascular and cardiac dysfunction. Conclusions: In conclusion, our study shows for the first time the beneficial effects of chronic ivabradine treatment on the progression of cardiac vascular complications in DMD and this may present a novel therapeutic approach. Further studies are needed to clarify the underling signalling mechanisms.